SERPENT IN THE BREAST - Saleem, Talha Bin; Ahmed, Irfan (Journal of Ayub Medical College Abbottabad, 2006)
Introduction: Dracunculus medinensis better known as guinea worm is the longest nematode infecting humans. Mature female worms migrate along subcutaneous tissue to reach the skin below the knee forming a painful ulcerating blister. Calcified male worm can occasionally be found in the retro peritoneum. Finding of a calcified worm in the breast tissue is very rare. Material and methods : We report a case of a fit and well African lady who was found to have a calcified guinea worm in the breast on a mammographic examination for investigation of a breast lump. Conclusion: Guinea worm can be included in the differential diagnosis of the breast lump especially in the endemic areas although the finding remains very rare. Key Words: Guinea worm, Dracunculus medinensis, Breast lump, Serpent.